2017
DOI: 10.1037/ccp0000151
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic randomized clinical trial of behavioral activation for depressed pregnant women.

Abstract: Objective Depression among pregnant women is a prevalent public health problem associated with poor maternal and offspring development. Behavioral Activation (BA) is a scalable intervention aligned with pregnant women’s preference for non-pharmacological depression care. This is the first test of the effectiveness of BA for depression among pregnant women, which aimed to evaluate the effectiveness of BA as compared with treatment as usual (TAU). Method Pregnant women (mean age = 28.75; SD = 5.67) with depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 65 publications
5
97
0
2
Order By: Relevance
“…At the same time, our mediation analysis suggested that patient-reported levels of behavioural activation at 3 months mediated the effects of HAP in reducing depression severity at 12 months. This suggests that behavioural activation may underlie HAP’s sustained effects and, thus, adds to existing evidence suggesting that patient-reported activation levels mediate response to behavioural activation therapy as specified by theory [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 56%
“…At the same time, our mediation analysis suggested that patient-reported levels of behavioural activation at 3 months mediated the effects of HAP in reducing depression severity at 12 months. This suggests that behavioural activation may underlie HAP’s sustained effects and, thus, adds to existing evidence suggesting that patient-reported activation levels mediate response to behavioural activation therapy as specified by theory [ 47 , 48 ].…”
Section: Discussionsupporting
confidence: 56%
“…Feasibility of study Feasibility will be defined according to several metrics, including feasible recruitment, enrollment, and retention. Estimates are derived from previous longitudinal studies with pregnant women [65,[87][88][89][90]. Feasible recruitment will be defined as identifying at least 480 potentially eligible patients based upon medical record review by research staff to approach during the prenatal intake visit.…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Acceptability of IPT Acceptability will first be measured by IPT session attendance. Acceptable IPT session attendance will be defined by 50% of participants randomized to IPT attending 5 or 6 (≥ 80%) of the total 6 sessions [87][88][89][90]. Acceptability will also be measured by participant ratings on a program acceptability interview adapted for the current study from the Treatment Process Questionnaire and administered by a project staff at the end of treatment assessment [66].…”
Section: Primary Outcomesmentioning
confidence: 99%
“…Each therapy session is video and audio-recorded and at least 20% of sessions will be randomly selected for fidelity ratings. Skill acquisition and fidelity is assessed using the Quality of Behavioral Activation Scale (Q-BAS) for BA (66)(67)(68) and a fidelity form created for the EXP treatment by RLA in consultation with MGC and KWT. Fidelity ratings will be provided by experts in each therapy (KWT; CM) or their trainees.…”
Section: Here]mentioning
confidence: 99%